Principals' interpersonal communication patterns in implementing academic supervision of beginning teachers - Yohanes Budi Listianto; Edi Harapan; Heri Setyo Nugroho (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study aims to describe the principal's interpersonal communication patterns in implementing academic supervision for novice teachers at SD Negeri 12 Muara Padang, recognizing that supervision quality extends beyond formal procedures. Employing a qualitative case study design, data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, display, and conclusion drawing. The findings reveal that the principal's interpersonal communication patterns were predominantly open, empathetic, supportive, positive, and egalitarian. During the pre-conference stage, the principal-built novice teachers' psychological readiness through friendly approaches and collaborative determination of supervision focus. In the observation stage, proper supervisory ethics and calming nonverbal communication were maintained. During the post-conference stage, feedback was delivered reflectively, dialogically, and constructively. These patterns significantly enhanced novice teachers' confidence, comfort, and performance, particularly in lesson planning and classroom instruction. This study offers a contextualized model of interpersonal communication in supervision specific to novice teachers in rural elementary schools, an area rarely examined qualitatively. Findings emphasize that principals must prioritize relational communication skills alongside technical supervisory competencies to effectively support early-career teachers. This research contributes empirical evidence that effective academic supervision is fundamentally determined by the quality of interpersonal communication, providing actionable guidance for school leaders and teacher training institutions in designing supervision frameworks that are both procedurally sound and relationally sensitive.